2006
DOI: 10.1093/rheumatology/kel072
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of soluble receptor activator of nuclear factors- B ligand (sRANKL) and reduced bone mineral density in patients with ankylosing spondylitis (AS)

Abstract: About 74% of AS patients have reduced BMD and this change reflects disease activity. Serum sRANKL levels and sRANKL/OPG ratios are up-regulated in patients with AS and have relationship with BMD and radiological changes. These results suggest that the imbalance between RANKL and OPG might be involved in the pathogenesis and clinical courses of osteoporosis in AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
2
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 13 publications
5
52
2
18
Order By: Relevance
“…RANKL is an essen ti al fac tor for os te oc lasts' ac ti vi ti es; 17 the re fo re, the sig ni fi cant re duc ti on ob ser ved in sRANKL le vels in HIG and LIG may be exp la i ned with the po si ti ve ef fects of re sis tan ce tra i ning on bo ne for ma ti on. The re fo re, con si de ring the high le vels of sRANKL be ing re la ted to so me di se a ses, [63][64][65] doing exer ci ses ef fec ti ve in re du cing sRANKL le vels may be pro tec ti ve aga inst the se di se a ses, and in directly aga inst bo ne loss or os te o po ro sis. Ho we ver, the re duc ti on ob ser ved in our CG is so mew hat diffi cult to exp la in.…”
Section: Opg-ranklmentioning
confidence: 95%
See 1 more Smart Citation
“…RANKL is an essen ti al fac tor for os te oc lasts' ac ti vi ti es; 17 the re fo re, the sig ni fi cant re duc ti on ob ser ved in sRANKL le vels in HIG and LIG may be exp la i ned with the po si ti ve ef fects of re sis tan ce tra i ning on bo ne for ma ti on. The re fo re, con si de ring the high le vels of sRANKL be ing re la ted to so me di se a ses, [63][64][65] doing exer ci ses ef fec ti ve in re du cing sRANKL le vels may be pro tec ti ve aga inst the se di se a ses, and in directly aga inst bo ne loss or os te o po ro sis. Ho we ver, the re duc ti on ob ser ved in our CG is so mew hat diffi cult to exp la in.…”
Section: Opg-ranklmentioning
confidence: 95%
“…Pre vi ous re se arch ha ve in di ca ted that BMD is po si ti vely 60 or ne ga ti vely 22 re la ted or not re la ted [25][26][27]30,61 to serum OPG le vels. Pa ti ents with low BMD at so me cer ta in si tes ha ve de mons tra ted hig her OPG 62 and sRANKL le vels; [63][64][65] or ne ga ti ve cor re la ti ons bet ween se rum OPG and RANKL le vels with BMD. 66 The se ne ga ti ve cor re la ti ons enab led the re se arc hers to pro po se a hypot he sis that sRANKL is in in ver se re la ti ons hip with BMD, ref lec ting the ex tent of oste oc las to ge ne sis and OPG might be in cre a sed as the com pen sa tory mec ha nism aga inst the ac ti vity of RANKL, to re du ce bo ne re sorp ti on.…”
Section: Opg-ranklmentioning
confidence: 99%
“…Osteoporosis of the femoral neck occurs in one third of patients, with osteopenia afflicting a further 41%. The lower bone mineral density in these patients seems related to the activity and severity of the underlying inflammatory process, 57 although the mechanism remains unclear. Heightened levels of the soluble receptor activator of N-␤ ligand promote osteoclast activity despite normal osteoprotegerin levels that antagonize osteoclast activity, creating a homeostatic perturbation towards bone resorption.…”
Section: Neurosurg Focus / Volume 24 / January 2008mentioning
confidence: 98%
“…[14,15] These findings led to the discovery of a new T-cell subset, the Th17 cells, by two separate study groups in 2005, and this subset makes the signature cytokine IL-17. Since then, more and more evidence has shown that this subset is often the principal cause of Interleukin-17 has previously been demonstrated to exist in the synovial fluid of patients with early or established RA [16,17] as well as in patients with AS [18,19] and SLE. [20] The Th17 subset has a functional reciprocal interrelationship with the classic Th1, Th2, and Treg cells, which are important players in the regulation of immune responses.…”
Section: Discussionmentioning
confidence: 99%